PENERAPAN ALGORITMA GENETIKA UNTUK KOMPRESI CITRA FRAKTAL - Indah Ciptayani, Putu; Firdaus Mahmudy, Wayan; Wahyu Widodo, Agus (Jurnal Ilmu Komputer; Vol. 2, No. 1 April 2009)
Fractal image compression is one of compression techniques which produce a high compression ratio with good quality of result image. But this method has weakness is the time to compress image is too long because checking domain and range block is done by brute force method. Because of it, necessary to get approach with genetic algorithm which genetic algorithm is an appropriate approach for complex combinatorial problem. Genetic algorithm play role in searching the matching domain and range block. Experiment is done by use three crossover and mutation method, the size of range block is 4, mutation probability is 0.1, crossover probability is 0.5, 0.6, 0.7, 0.8, 0.9 and 1.0. Maximal size of generations are 500. The best result of compression image has ratio 75.01% with compression time is 10.7 second and MSE is 0.158839.